Resilience framework and metrics for energy master planning of communities. (15th July 2020) - Charani Shandiz, Saeid; Foliente, Greg; Rismanchi, Behzad; Wachtel, Amanda; Jeffers, Robert F.
Abstract: Changes in the nature, intensity, and frequency of climate-related extreme events have imposed a higher risk of failure on energy systems, especially those at the community level. Furthermore, the evolving energy demand patterns and transition towards renewable and localised energy supply can affect energy system resilience. How can an energy system be planned and reconfigured to address these challenges without compromising the system's resilience against chronic stresses and extreme events? Unlike energy system reliability, resilience is neither a common nor an explicit consideration in energy master planning at the community level. In addition, there is no universally agreed-upon method or metrics for measuring or estimating resilience and defining mitigation strategies. This paper introduces a multi-layered energy resilience framework and set of metrics for energy master planning of communities, including the new generation of district energy systems. The potential system disturbances and their short and long-term impacts on various components of the energy system are discussed for commonly expected and extreme events. Three layers of energy resilience are discussed: engineering-designed resilience, operational resilience, and community-societal resilience. A starting set of energy resilience metrics to support engineering design and energy master planning for communities is identified. Implications for future research and practice are noted. Highlights: A novel resilience framework is proposed for community-level energy master planning. It consists of three layers: engineering, operational and community resilience. Energy resilience planning steps are introduced and a set of metrics is identified. This can potentially enhance system resilience planning of community-level systems. The practical framework applications and implications are explored.